Pengembangan Profesional Kepala Sekolah di Madrasah MAS Bustaanul Uluum : Tantangan dan Peluang - Inom Nasution; Budi Budi; Anggi Gusrina Simatupang (Jurnal Bintang Pendidikan Indonesia, 2024)
The research that has been carried out is entitled "Professional Development of School Principals at Madrasah Mas Bustaanul Uluum: Challenges and Opportunities". This research aims to: find out how professional school principals are able to answer the challenges of current developments. find out how professional school principals take advantage of various opportunities in facing the challenges of current developments. To obtain data in this research the author used qualitative research methods from data produced through observation, interviews and documentation. The data analysis used is data reduction, data presentation and drawing conclusions. This research was carried out in the principal's office. The results of this research reveal several findings: (1) There is an important leadership role for professional school principals at MAS Bustaanul Uluum Teluk Dalam. (2) Efforts of Professional School Principals in Facing the Challenges of Progress in Educational Technology. (3) There are opportunities to face the challenges of development and progress in educational technology.